Silent Myocardial Ischemia and left Ventricular Diastolic Dysfunction in Type 2 Diabetic Patients. A Case Control study - Walinjom, Joshua Njimbuc; Boombhi, Jerome; Etoa, Martine; Ambe, Collins Chenwi; Eho, Emerentia; Menanga, Alain; Kingue, Samuel (Cardiology and Cardiovascular Medicine, 2024)
Aims: People with type 2 diabetes mellitus (T2DM) have a higher cardiovascular morbidity and mortality. We sought to describe the occurrence of asymptomatic Left Ventricular Diastolic Dysfunction (LVDD) and silent Myocardial infarction (SMI) in diabetic patients in comparison with non-diabetic controls. Methods: From March 2019 to September 2020, transthoracic 2D doppler, tissue doppler echocardiography and an exercise stress test (EST) were used to assess LVDD and SMI in diabetics (cases) and non-diabetics (controls). P values <0.05 were considered statistically significant. Results: In total,166 participants were recruited, 95 cases and 71 controls, matched for age and sex: mean age 43 ± 7 years in cases and 40 ± 5 years in controls, p>0.05. LVDD was significantly higher in cases (n=22; 23.2%; 95%CI:15.4%-33.2%) as compared to healthy controls (n=6; 8.5%; 95% CI:3.5%-18.1%), p<0.05. Similarly, SMI was significantly higher in diabetic patients (n=13; 13.7%; 95% CI:7.8%-22.6%) as compared to the non-diabetic controls (n=2; 2.8%; 95% CI:0.5%-10.7%), p<0.05. Conclusions: Diabetic patients have higher rates of LVDD and SMI, therefore requiring closer clinical and paraclinical follow-up for good long-term outcomes.